2019
DOI: 10.1136/bmjopen-2018-025979
|View full text |Cite
|
Sign up to set email alerts
|

Size, composition and distribution of human resource for health in India: new estimates using National Sample Survey and Registry data

Abstract: ObjectivesWe provide new estimates on size, composition and distribution of human resource for health in India and compare with the health workers population ratio as recommended by the WHO. We also estimate size of non-health workers engaged in health sector and the size of technically qualified health professionals who are not a part of the health workforce.DesignNationally representative cross-section household survey and review of published documents by the Central Bureau of Health Intelligence.SettingNati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
110
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(118 citation statements)
references
References 11 publications
6
110
2
Order By: Relevance
“…The findings of this study are in line with the latest research findings in India (Singh, 2019;Karan et al, 2019) and China (Zhu, Hsieh and Mao, 2019). The results of the study in the two regions found the same research facts, that the distribution of physicians was influenced by the population in an area.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of this study are in line with the latest research findings in India (Singh, 2019;Karan et al, 2019) and China (Zhu, Hsieh and Mao, 2019). The results of the study in the two regions found the same research facts, that the distribution of physicians was influenced by the population in an area.…”
Section: Discussionsupporting
confidence: 89%
“…Especially access to basic health services that require more attention in terms of geography. Special efforts or policies are still needed to deal with the problem of doctor distribution, especially in the era of National Health Insurance (Karan et al, 2019). The purpose of this study is to answer any factors related to the distribution of doctors by the province in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent estimate based on NSSO data shows there were 3.82 million health workforce belonged to different categories in 2016. 7 This figure is lower by almost 33.45% of health workforce registered with various councils and associations in the country during 2017 (Table 2).…”
Section: Size and Compositionmentioning
confidence: 93%
“…2,3,6 RMPs act as the first point of contact for treatment of a significant proportion of population living in rural and far flung areas. 7 Nurses have a diploma in general nursing and midwifery or a bachelor's degree or a postgraduate degree registered with the Indian Nursing Council (INC). Another group of health workforce consists of auxiliary nurses and midwives (ANMs), who work as subordinates to the main nurse, possess a diploma in auxiliary nurse midwifery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation